A method for reducing the surface roughness of fiber-reinforced resin-based wave-transmitting composite materials
By grinding the surface of the fiber-reinforced resin-based wave-transmissive composite material, plasma treatment, spraying silane coupling agent and thermoplastic resin to form a polymer film, the problem of high surface roughness of the composite material is solved and the improvement of surface uniformity and dielectric properties is achieved.
Patent Information
- Application Number
- CN202210961990.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-08-11
AI Technical Summary
The surface roughness of the fiber-reinforced resin-based wave-transmissive composite material has high surface roughness, which affects the construction quality of subsequent functional layers. In addition, existing improvement methods such as scraping putty layers have problems such as affecting dielectric properties and cumbersome processes.
By grinding the surface of the fiber-reinforced resin-based wave-transmissive composite material, the resin-rich layer and the release agent are removed, then air plasma treatment is performed and the silane coupling agent solution is sprayed to form an adhesive interface layer, and finally the thermoplastic resin solution is sprayed and cured to form a polymer film to improve surface quality.
It significantly reduces the surface roughness of the composite material, improves surface uniformity, and does not affect the dielectric properties of the composite material. It is suitable for subsequent metallization, patterning and functionalization treatments.
Smart Images

Figure CN115447171B_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a method for reducing the surface roughness of a fiber-reinforced resin-based wave-transmitting composite material, and belongs to the technical field of surface modification of a fiber-reinforced resin-based wave-transmitting composite material. Background Art
[0002] Fiber-reinforced resin-based wave-transmitting composite materials are high-performance composite materials with quartz fiber or glass fiber as reinforcement and thermosetting resin as matrix. They have excellent mechanical properties, heat resistance, wave-transmitting properties and fatigue resistance, and have become the main material for manufacturing high-performance radomes. However, due to its structural composition and molding process, fiber-reinforced resin-based wave-transmitting composite materials have poor surface quality and many surface defects, mainly including unevenly distributed fiber-rich and resin-rich areas, ups and downs caused by fiber woven structures, and a large number of microporous structures on the surface. These defects significantly increase the surface roughness of fiber-reinforced resin-based wave-transmitting composite materials, affecting the construction quality of subsequent composite surface electromagnetic functional layers, antistatic layers, rain erosion protection layers and other functional coatings.
[0003] At present, the commonly used method to improve the surface defects of composite materials is to apply a putty layer. However, the inorganic fillers contained in the putty layer usually have a high dielectric constant and dielectric loss, which has an adverse effect on the wave transmission performance of the composite material. In addition, the presence of inorganic fillers in the putty layer makes the surface roughness of the modified composite material limited and the surface uniformity poor. Moreover, the process of applying putty is cumbersome, inefficient, and poor in surface adaptability. Therefore, it is urgent to develop a simple, effective, and surface-adaptable method for reducing the surface roughness of fiber-reinforced resin-based wave-transmitting composite materials. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a surface modification method suitable for fiber-reinforced resin-based wave-transparent composite materials, which can effectively reduce the surface roughness of the composite material and improve the surface uniformity without affecting the dielectric properties of the wave-transparent composite material.
[0005] The present invention relates to a method for reducing the surface roughness of a fiber-reinforced resin-based wave-transmitting composite material, which specifically comprises the following steps:
[0006] Step 1: Grinding the surface of the fiber-reinforced resin-based wave-transmitting composite material to remove the resin-rich layer and the release agent on the surface;
[0007] Step 2: After polishing, the surface of the composite material is treated with air plasma to improve the surface energy of the composite material, and then a silane coupling agent solution is sprayed thereon to form a bonding interface layer after drying. The plasma treatment can improve the wetting and spreading of the silane coupling agent solution on the composite material;
[0008] Step 3: Spray a thermoplastic resin solution on the surface of the bonding interface layer, and form a polymer film on the surface of the composite material through high-temperature curing to complete the surface modification.
[0009] Preferably, in step 1, the surface of the fiber-reinforced resin-based wave-transparent composite material is coarsely ground with sandpaper of 100 to 400 meshes, and the surface of the fiber-reinforced resin-based wave-transparent composite material is finely ground with sandpaper of 600 to 1000 meshes to remove the resin-rich layer and the release agent on the surface.
[0010] Preferably, in step 2, the silane coupling agent solution is prepared by adding the silane coupling agent into anhydrous ethanol and mixing the mixture uniformly by magnetic stirring.
[0011] Preferably, in step 2, the silane coupling agent includes but is not limited to one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethylsilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-ureapropyltrimethoxysilane, octyltriethoxysilane, dimethyldimethoxysilane, methyltributylidene oxime silane or isocyanatepropyltriethoxysilane.
[0012] Preferably, in step 2, the concentration of the silane coupling agent solution is 30% to 60%.
[0013] Preferably, in step 2, the spraying amount of the silane coupling agent is 0.01-0.1 ml / cm 2 .
[0014] Preferably, the drying temperature in step 2 is 40-80° C., the drying time is 1-2 hours, and the drying equipment used is a forced air oven.
[0015] Preferably, in step 3, the preparation method of the thermoplastic resin solution is: adding the thermoplastic resin into an organic solvent, heating and stirring to completely dissolve the thermoplastic resin, and cooling to room temperature for standby use.
[0016] Preferably, in step 3, the thermoplastic resin includes: one of phenoxy resin, polyimide resin, polyaryletherketone resin, polytetrafluoroethylene resin, polyvinylidene fluoride resin, polyarylate resin, polyethylene resin, and polyvinyl chloride resin.
[0017] Preferably, in step 3, the organic solvent of the thermoplastic resin is one or more of ethanol, acetone, butanone, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, diethylene glycol methyl ether, ethyl acetate, dimethylacetamide, and dimethylformamide.
[0018] Preferably, the concentration of the thermoplastic resin solution in step 3 is 5% to 20%wt.
[0019] Preferably, the spraying amount of the thermoplastic resin in step 3 is 0.1-0.5 ml / cm 2 .
[0020] Preferably, the curing in step 3 includes two stages, the first stage is a pretreatment stage, the temperature of which is 40-80°C and the time is 8-12 hours, and the second stage is a high temperature treatment stage, the temperature of which is 120-250°C and the time is 2-4 hours. The staged curing process can significantly reduce defects such as pinholes and shedding, thereby improving the quality of the polymer coating.
[0021] The present invention also provides a fiber-reinforced resin-based wave-transmitting composite material with reduced surface roughness, which is prepared according to the above method.
[0022] The beneficial effects of the present invention are:
[0023] The present invention can significantly improve the surface quality of the fiber-reinforced resin-based composite material surface, reduce surface roughness, and improve surface uniformity, while not affecting the dielectric properties of the composite material, thereby not reducing the wave transmission performance of the composite material, and laying the foundation for subsequent surface metallization, patterning and functionalization of the composite material. The method has the advantages of simple process, high efficiency, and strong adaptability to curved surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope photograph of the surface of the composite material in Example 1.
[0025] Figure 2 This is the optical three-dimensional contour diagram of the composite material surface in Example 1.
[0026] Figure 3 This is a scanning electron microscope image of the modified composite material in Example 1.
[0027] Figure 4 This is a photo of the surface optical profile of the modified composite material in Example 1. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below through specific embodiments and drawings.
[0029] Example 1
[0030] The quartz fiber reinforced cyanate ester composite plate was prepared by vacuum bag pressing process. Figure 1 This is a scanning electron microscope photo of the composite material surface. Figure 2The optical three-dimensional profile of the composite surface. The composite surface was roughly ground with 100-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 600-grit sandpaper to improve the surface flatness.
[0031] 30 g of γ-aminopropyltriethoxysilane was dissolved in 70 g of ethanol, and magnetic stirring was performed at room temperature to obtain a silane coupling agent solution.
[0032] The polished composite surface is treated with air plasma, and then the silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer, i.e., a bonding interface layer, is constructed on the composite surface after treatment at 40°C / 1 hour.
[0033] 5 g of thermoplastic polyaryletherketone resin was dissolved in 95 g of dimethylacetamide, and the mixture was evenly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0034] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 40°C and the time is 8 hours, and the second stage is a high temperature treatment stage, the temperature of which is 120°C and the time is 2 hours. Figure 3 The scanning electron microscope image of the modified composite material is shown in Figure 2. Figure 4 This is the optical profile photo of the modified composite material surface.
[0035] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0036] Example 2
[0037] The quartz fiber reinforced cyanate ester composite plate was prepared by autoclave process. The composite surface was roughly ground with 100-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 600-grit sandpaper to improve the surface flatness.
[0038] 30 g of γ-aminopropyltriethoxysilane was dissolved in 20 g of ethanol and stirred with magnetic force at room temperature to obtain a silane coupling agent solution.
[0039] The polished composite surface is treated with air plasma, and then a silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer is constructed on the composite surface after the treatment at 80°C for 2 hours.
[0040] 20 g of thermoplastic polyaryletherketone resin was dissolved in 80 g of dimethylacetamide, and the mixture was evenly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0041] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 50°C and the time is 9 hours, and the second stage is a high temperature treatment stage, the temperature of which is 140°C and the time is 3 hours.
[0042] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0043] Example 3
[0044] The quartz fiber reinforced polyarylene composite plate was prepared by resin transfer molding process. The composite surface was roughly ground with 100-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 600-grit sandpaper to improve the surface flatness.
[0045] 30 g of γ-aminopropyltriethoxysilane was dissolved in 70 g of ethanol, and magnetic stirring was performed at room temperature to obtain a silane coupling agent solution.
[0046] The polished composite surface is treated with air plasma, and then a silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer is constructed on the composite surface after the treatment at 40°C for 1 hour.
[0047] 5 g of thermoplastic polyimide resin was dissolved in 95 g of dimethylacetamide, and the mixture was evenly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0048] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 60°C and the time is 10 hours, and the second stage is a high temperature treatment stage, the temperature of which is 160°C and the time is 2 hours.
[0049] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0050] Example 4
[0051] The quartz fiber reinforced cyanate ester composite flat plate was prepared by vacuum bag pressing process. The composite surface was roughly ground with 400-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 1000-grit sandpaper to improve the surface flatness.
[0052] 30 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was dissolved in 70 g of ethanol and stirred with magnetic force at room temperature to obtain a silane coupling agent solution.
[0053] The polished composite surface is treated with air plasma, and then the silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer, i.e., a bonding interface layer, is constructed on the composite surface after treatment at 60°C / 1 hour.
[0054] 5 g of thermoplastic polytetrafluoroethylene resin was dissolved in 95 g of ethylene glycol monomethyl ether, and the mixture was evenly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0055] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 70°C and the time is 11 hours, and the second stage is a high temperature treatment stage, the temperature of which is 200°C and the time is 4 hours.
[0056] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0057] Example 5
[0058] The quartz fiber reinforced cyanate ester composite flat plate was prepared by vacuum bag pressing process. The composite surface was roughly ground with 200-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 800-grit sandpaper to improve the surface flatness.
[0059] 40 g of γ-(methacryloyloxy)propyltrimethoxysilane was dissolved in 60 g of ethanol, and magnetic stirring was performed at room temperature to obtain a silane coupling agent solution.
[0060] The polished composite surface is treated with air plasma, and then the silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer, i.e., a bonding interface layer, is constructed on the composite surface after treatment at 80°C / 1 hour.
[0061] 10 g of thermoplastic phenoxy resin was dissolved in 90 g of acetone, and the mixture was evenly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0062] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 80°C and the time is 12 hours, and the second stage is a high temperature treatment stage, the temperature of which is 220°C and the time is 3 hours.
[0063] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0064] Example 6
[0065] The quartz fiber reinforced cyanate ester composite flat plate was prepared by vacuum bag pressing process. The composite surface was roughly ground with 300-grit sandpaper to remove the release agent and the resin-rich layer, and then the composite surface was further polished with 900-grit sandpaper to improve the surface flatness.
[0066] 50 g of γ-ureapropyltrimethoxysilane was dissolved in 50 g of ethanol, and the solution was obtained by magnetic stirring at room temperature.
[0067] The polished composite surface is treated with air plasma, and then the silane coupling agent solution is sprayed on the composite surface after the air plasma treatment, and a silane coupling agent transition layer, i.e., a bonding interface layer, is constructed on the composite surface after treatment at 80°C / 1 hour.
[0068] 10 g of thermoplastic polyarylate resin was dissolved in 90 g of ethyl acetate, and the mixture was uniformly mixed by magnetic stirring at room temperature to obtain a thermoplastic coating.
[0069] The prepared thermoplastic coating is sprayed on the surface of the composite material modified by the silane coupling agent, and the modified composite material is obtained by curing. The curing includes two stages, the first stage is a pretreatment stage, the temperature of which is 80°C and the time is 12 hours, and the second stage is a high temperature treatment stage, the temperature of which is 250°C and the time is 4 hours.
[0070] The surface roughness values of the composite materials before and after modification are listed in Table 1.
[0071] Table 1 Surface roughness of composite materials before and after modification
[0072]
[0073] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for reducing the surface roughness of a fiber-reinforced resin-based wave-transmitting composite material, characterized in that: The following steps are involved: Grinding the surface of the fiber-reinforced resin-based wave-transmitting composite material: Use 100-400 mesh sandpaper to roughly grind the surface of the fiber-reinforced resin-based wave-transmitting composite material to remove the resin-rich layer and release agent on the surface; Then, the surface of the fiber-reinforced resin-based wave-transmitting composite material was finely ground with 600-1000 mesh sandpaper to improve the surface flatness; Air plasma treatment is performed on the polished composite surface, and then a silane coupling agent solution is sprayed, and a bonding interface layer is formed after drying; A thermoplastic resin solution is sprayed on the surface of the bonding interface layer, and a polymer film is formed on the surface of the composite material through high-temperature curing to complete the surface modification; the curing includes two stages, the first stage is a pretreatment stage, the temperature of the pretreatment stage is 40-80°C, and the time is 8-12 hours; the second stage is a high-temperature treatment stage, the temperature of the high-temperature treatment stage is 120-250°C, and the time is 2-4 hours.
2. The method according to claim 1, characterized in that: The preparation method of the silane coupling agent solution is as follows: adding the silane coupling agent to anhydrous ethanol and mixing them evenly by magnetic stirring; the concentration of the silane coupling agent solution is 30% to 60%; the spraying amount of the silane coupling agent is 0.01 to 0.1 mL / cm 2 .
3. The method according to claim 1, characterized in that The silane coupling agent includes at least one of the following: γ-aminopropyltriethoxysilane, γ-aminopropyltrimethylsilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-ureapropyltrimethoxysilane, octyltriethoxysilane, dimethyldimethoxysilane, methyltributylidene oxime silane, and isocyanatepropyltriethoxysilane.
4. The method according to claim 1, characterized in that: The drying temperature is 40-80° C., the drying time is 1-2 hours, and the drying equipment used is a blast oven.
5. The method according to claim 1, characterized in that The preparation method of the thermoplastic resin solution is as follows: adding the thermoplastic resin into an organic solvent, heating and stirring to completely dissolve the thermoplastic resin, and cooling to room temperature for standby use; the concentration of the thermoplastic resin solution is 5% to 20%; the spraying amount of the thermoplastic resin is 0.1 to 0.5 mL / cm 2 .
6. The method according to claim 1, characterized in that The thermoplastic resin includes at least one of the following: phenoxy resin, polyimide resin, polyaryletherketone resin, polytetrafluoroethylene resin, polyvinylidene fluoride resin, polyarylate resin, polyethylene resin, polyvinyl chloride resin.
7. The method according to claim 1, characterized in that The organic solvent of the thermoplastic resin is at least one of the following: ethanol, acetone, butanone, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, diethylene glycol methyl ether, ethyl acetate, dimethylacetamide, and dimethylformamide.
8. A fiber-reinforced resin-based wave-transmitting composite material with reduced surface roughness obtained according to the method of any one of claims 1 to 7.
Citation Information
Patent Citations
Method for improving bonding strength of sprayed coating on surface of resin-based composite material
CN107552360A